Severe Acute Respiratory Syndrome Coronavirus 2 Antibodies in Adults in Madrid, Spain - Soriano, Vicente; Meiriño, Rosa; Corral, Octavio Jorge; Guallar, María Pilar (Clinical infectious diseases, 2021)
We read with interest the article by Huff and Singh [1] in which they highlight the role of asymptomatic transmissions of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The authors point out that “public health strategies relying solely on ‘symptom onset’ for identification of new cases need urgent reassessment.” We want to add that information derived from antibody testing may help to obtain a better picture of the coronavirus spread in a given regionMadrid has been the region most severely hit by coronavirus disease 2019 (COVID-19) in Spain, with 65 000 confirmed cases and 9000 deaths as of 10 May 2020, 8 weeks after implementation of the country’s lockdown on 14 March [2]. We wanted to know to what extent these figures translated into high rates of antibody detection in the community, additionally unveiling asymptomatic cases and persons with symptoms who could not be tested due to a shortage of diagnostic tests at the peak of the epidemic.
Keywords: coronavirus 2; antibodies; severe acute respiratory syndrome; Scopus(2); WOS(2)